Minat Siswa Sekolah Menengah Atas dalam Mengikuti Jong Batak Art Festival IV di Taman Budaya Sumatera Utara - Erfinaika Siringoringo; Uyuni Widiastuti; Lamhot Basani Sihombing (Gondang: Jurnal Seni dan Budaya, 2019)
This study aims to determine the interest of YP high school students. HKBP Sidorame in following Jong Batak Art Festival IV in the North Sumatra Cultural Park and the factors that influenced the interest of YP High School students. HKBP Sidorame in following Jong Batak Art Festival IV in North Sumatra Cultural Park. The theory used in this study is the theory of interest, kinds of interests, influencing factors, jong batak which explains the feeling of being more like and feeling interested in something or activity, without being told. Basically, interest is the acceptance of a relationship between yourself and something outside of yourself, the stronger or nearer the relationship, the greater the interest. The method in this study is mixed methods. Data collection is based on library studies, observation, and documentation. The sample in this study were students of class XII IPS 1 totaling 32 people. Based on the results of the research conducted, it can be seen that the use of questionnaires as research instruments shows that students are interested in participating in the Jong Batak Art Festival IV but have not reached the highest level in the assessment category, which is Very Interested.